Improvement in thermal properties of PCM/Expanded vermiculite/expanded graphite shape stabilized composite PCM for building energy applications - Rathore P.K.S.; Shukla S.K. (My University, 2025)
This work investigates the combined effect of loading Expanded Graphite (EG) and Expanded Vermiculite (EV) on the thermophysical properties of the low-cost commercially available PCM (OM37) and there capability of regulating the indoor temperature when embedded in the building element. Shape Stabilized Composite Phase Change Material (ss-CPCM) was prepared using PCM, EV, and EG through physical blending followed by vacuum impregnation. Latent heat storage capacity, phase change parameters, melting and freezing response, thermal stability, thermal reliability, and leakage proof performance was investigated. Melting enthalpy of 114.23 J/g, 111.56 J/g, 105.08 J/g, and 99.32 J/g at melting temperature of 40.61 °C, 39.12 °C, 38.83 °C, and 37.41 °C was obtained for ss-CPCM-1, 3, 5, and 7 respectively. A rise of 114.4% in the thermal conductivity was observed by adding 7 wt% of EG in ss-CPCM. ss-CPCM loaded with 7 wt% of EG heats 25.9% faster and cools 19.2% faster in comparison to pristine PCM. The prepared ss-CPCM preserves its thermal characteristics even after 1000 heating and cooling cycles. Moreover, when embedded in the wallboard, the ss-CPCM-7 has shown the excellent capability of regulating indoor temperature. © 2021 Elsevier Ltd